A Social Science Index and Conceptual Framework for Assigning Weights in Surf Tourism Planning and Development. Issue 3 (4th May 2019) - Martin, Steven Andrew; Ritchie, Raymond
ABSTRACT: This paper develops a social science weighting schema for surf tourism planning and sustainable development, eco-tourism, and conservation studies using surf tourism as a representative worked example. Assessment scores from a previously published surf resource sustainability field study of nine beaches in Phuket, Thailand, were weighted against data taken from surveys of expert scholars and surfers from a range of diverse backgrounds. The study measured levels of significance among weighted and unweighted means and bias ratio for 27 social, economic, environmental and governance indicators. Differences between scores and weighted scores were, in general, low, but this was not the case in key areas of concern, notably governance, and areas where poor governance had negative consequences, such as water quality. The findings indicate that analysis of weighted data helps identify key metrics. We show that analysis of weighted data provides insights not apparent from working on unweighted data. The procedures and weighting strategies employed in this research can be used for tourism planning and other related research activities which use interview data, such as research on, ecotourism, national park surveys, amateur fishing, snorkeling and reef tours. This study provides a conceptual framework for comparisons of different studies using similar protocols.